Communism and anti-Communism in early Cold War Italy : language, symbols and myths - Mariuzzo, Andrea, 1979- (Manchester : Manchester University Press, 2018)
The books detects the struggle of Communism and anti-Communism as a key feature for the making of the political system in post-WWII democratic Italy, and presents it in its international context through a broad analysis of the main communication networks.
Front matter; Cover; Half Title; Title Page; Copyright Page; Contents; Figures; Abbreviations; Introduction; Systems and methods for political communication in post-war Italy; Religious and moral values; Freedom and democracy; The fatherland, the Italian nation and its role in the world; Towards a legitimation of prosperity?; References; Index.
Includes bibliographical references and index.
Online resource; title from PDF title page (Ebsco, viewed September 13, 2018).
JSTOR
Keywords: Communication in politics -- Italy -- History -- 20th century; Communism -- Italy -- History -- 20th century; Anti-communist movements -- Italy -- History -- 20th century; Italy -- History -- 1945-; Italy -- Politics and government -- 1945-1976.; Communication politique -- Italie -- Histoire -- 20e siècle.; Anticommunisme -- Italie -- Histoire -- 20e siècle.; Italie -- Histoire -- 1945-; Italie -- Politique et gouvernement -- 1945-1976.; HISTORY -- Europe -- Italy; HISTORY -- General; Anti-communist movements; Communication in politics; Communism; Politics and government; Italy; Since 1900; Anti-Communism.; Catholic associations; Christian democracy; Cold War; Italian Communism; Political communication; Political culture; Political languages; Post-Second World War Italy; History